2019
DOI: 10.31086/tjgeri.2019150577
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Injuries Among The Elderly Admitted To The Emergency Department

Abstract: Occupational injuries are among the leading causes of morbidity and mortality worldwide. The rate of occupational injuries in the elderly is increasing daily and is directly proportional to the increase in the elderly population. This study aimed to examine occupational injuries in elderly patients (age, >65 years) admitted to the emergency department. Materials and Method: This cross-sectional study included 122 patients aged >65 yearold who were admitted to the third level emergency department with an occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
0
0
1
Order By: Relevance
“…In Parkinson's disease, leg muscles rigidity, blood pressure lowering effects of drugs and cognitive impairment increases the risk of falls (17). Savas S et al found that the frequency of falls in older patients was 35.7%, the presence of a history of falls was 24.3% and the frequency of fear of falling was 20.3%, in their study (18). All of these rates were much higher in our study.…”
Section: Discussionsupporting
confidence: 42%
“…In Parkinson's disease, leg muscles rigidity, blood pressure lowering effects of drugs and cognitive impairment increases the risk of falls (17). Savas S et al found that the frequency of falls in older patients was 35.7%, the presence of a history of falls was 24.3% and the frequency of fear of falling was 20.3%, in their study (18). All of these rates were much higher in our study.…”
Section: Discussionsupporting
confidence: 42%
“…İstanbul ilinde bir şantiyede yapılan çalışmada kazaların oluş şekilleri cisim çarpması %49,0 (n=100), sıkışma %12,3 (n=25), düşme %11,3 (n=23) olarak tespit edildi 19 . Salt ve ark.yaptığı çalışmada en sık yaralanma mekanizması aynı seviyeden ya da yüksekten düşme %56.7 (n=74) olarak görüldü 24 . Yapılan tüm çalışmalar göstermiştir ki işin şekli, çalışma koşulları, çalışılan alan, çalışılan makineler, çalışılan saatler iş yerinde oluşan kazaların oluş şekillerini belirlemektedir.…”
Section: Bulgularunclassified